ANALISIS KESEJAHTERAAN EKONOMI PELAKU USAHA SEWA MAINAN ALUN-ALUN SANGKALA BUANA CIREBON - Gama Pratama; Ade Nurkhafifah; Kamilah Marzuq; Lukman Nul Hakim; Nur Aisyah; Riana Adita; Putri Muliana Sari (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
Abstract. This research was conducted in October 2022. The purpose of this study was to analyze producer surplus and the welfare of toy rental business actors in Sangkala Buana Cirebon Square by using the interview method with 5 respondents who are toy rental business actors in the area. This research uses case study method. The data needed in this study includes primary data obtained directly from the field through the interview process. The results of the study show that the producer surplus is quite high for the toy rental business and the Sangkala Buana Cirebon Square area can be used as a place to open a business that promises profits like prosperity